2022
DOI: 10.1021/acs.jpcc.1c07098
|View full text |Cite
|
Sign up to set email alerts
|

Surface Wettability Drives the Crystalline Surface Assembly of Monodisperse Spheres in Evaporative Colloidal Lithography

Abstract: The wettability nature of substrates has been found to profoundly influence the surface assembly of monodisperse spherical particles for colloidal suspensions that are dried by evaporation to spontaneously form either periodic or disordered packing arrangements. The self-assembly of spheres has consequences when preparing surface masks for evaporative colloidal lithography. When a droplet of an aqueous suspension of monodisperse latex particles was dried by evaporation on flat substrates that are hydrophilic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
(84 reference statements)
0
12
0
3
Order By: Relevance
“…30–34 However, as the wet assembly techniques rely on optimized conditions, such as solvent evaporation rate, surface wettability, pH, it tends to be challenging to attain perfect ordered crystals, without any cracks, on a large scale. 35…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30–34 However, as the wet assembly techniques rely on optimized conditions, such as solvent evaporation rate, surface wettability, pH, it tends to be challenging to attain perfect ordered crystals, without any cracks, on a large scale. 35…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] However, as the wet assembly techniques rely on optimized conditions, such as solvent evaporation rate, surface wettability, pH, it tends to be challenging to attain perfect ordered crystals, without any cracks, on a large scale. 35 On the other hand, dry assembly methods such as the rubbing of dry particles, and vacuum-driven assembly of particles from generated clouds, have proven to be promising and faster routes to obtaining assembled particle arrays on surfaces. [36][37][38] In earlier reports, scientists primarily engaged in studying the gravity-dominated pattern formation that emerged when disordered granular packings comprising large, mm-sized spheres or binary grain mixtures on substrates were vibrated in lateral direction.…”
Section: Introductionmentioning
confidence: 99%
“… 18 20 Recent research has shown that the surface wettability has a significant effect on the self-assembly of spherical particles from colloidal suspensions upon evaporation. 21 Alternatively, a large-scale dry particle assembly process has been proposed by the Jeong group. 1 , 8 This was successfully applied for the formation of large-area colloidal monolayers on flat, curved, and prepatterned substrates by means of unidirectional rubbing of dry powder using an elastomeric material.…”
Section: Introductionmentioning
confidence: 99%
“…Particle arrays can, for example, be used in microengineering as a lithographic mask, allowing for the fabrication over a large area of micro- and nanostructures, such as three-dimensional inverse woodpile photonic crystals. , Next to this, the periodicity in the monolayers is an essential key feature in a vast number of applications, such as photonics, light manipulation devices, optical and biological sensors, wearable medical devices, chemical catalysis, superhydrophilic, superhydrophobic, or self-cleaning antireflective surfaces, and many more. , Finding generic particle assembly methods that are independent of the size and the material of the particles is hence of paramount importance. Over the past few decades, various techniques have been developed to find a reproducible and cheap way to assemble particles on a large scale in monolayers on flat substrates or in structured arrays on patterned substrates. Most studies exploit wet assembly techniques, such as Langmuir–Blodgett, evaporative slope self-assembly, dip-coating, drop-casting, , spin-coating, techniques involving the application of an electric field, , and many more. Recent research has shown that the surface wettability has a significant effect on the self-assembly of spherical particles from colloidal suspensions upon evaporation . Alternatively, a large-scale dry particle assembly process has been proposed by the Jeong group. , This was successfully applied for the formation of large-area colloidal monolayers on flat, curved, and prepatterned substrates by means of unidirectional rubbing of dry powder using an elastomeric material.…”
Section: Introductionmentioning
confidence: 99%
“…Evaporation of colloidal droplets has attracted increasing attention, not only because rich and diverse physical phenomena emerge, including the coffee ring effect, but also its widespread applications in industry, , such as printing and coating technologies, , medical diagnosis, and biochemical detection . To achieve a uniform and ordered pattern is becoming quite necessary for many potential applications, such as printed electronics, , because the high-quality printed structures are the foundation of high-performance devices …”
mentioning
confidence: 99%